2007
DOI: 10.1007/s00259-007-0457-7
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin receptor subtype 2-mediated uptake of radiolabelled somatostatin analogues in the human kidney

Abstract: Purpose Renal irradiation is a dose-limiting factor in peptide receptor radionuclide therapy using radiolabelled somatostatin analogues. This irradiation is mainly caused by reabsorption of radiolabelled peptides in the proximal tubule. In the human kidney, somatostatin receptors are expressed in the vasa recta, tubuli and glomeruli. It is not clear to what extent these receptors contribute to the total kidney radioactivity uptake. Methods Retrospectively, [ 111

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 37 publications
3
38
0
2
Order By: Relevance
“…Elevated renal uptake does not, however, preclude peptide-targeted radionuclides from clinical use. 111 In-octreotide scintigraphy is widely used clinically despite demonstrating high renal uptake (40). In the case of 89 Zr-αGPC3-F(ab′)2, clinical utility would likely be maintained because HCC rarely metastasizes to the kidneys (41).…”
Section: Discussionmentioning
confidence: 99%
“…Elevated renal uptake does not, however, preclude peptide-targeted radionuclides from clinical use. 111 In-octreotide scintigraphy is widely used clinically despite demonstrating high renal uptake (40). In the case of 89 Zr-αGPC3-F(ab′)2, clinical utility would likely be maintained because HCC rarely metastasizes to the kidneys (41).…”
Section: Discussionmentioning
confidence: 99%
“…Rolleman et al retrospectively studied 111 In-octreotide scans of patients who were scanned before and during treatment with unlabeled octreotide. A mean 18% reduction in kidney uptake during octreotide treatment was found, suggesting some involvement of somatostatin receptors in the renal uptake of 111 Inoctreotide (19). However, an excess of unlabeled octreotide may also interfere with binding of 111 In-octreotide to other receptors such as megalin.…”
Section: Proximal Tubular Reabsorption and Processingmentioning
confidence: 91%
“…Recent experimental observations have suggested that the multiligand megalin/cubilin receptor complex localized at the apical membrane of renal proximal tubules could be the transport mechanism responsible for resorption and retention of the radiolabeled somatostatin analogs [17,18]. In addition, subtype 2 of somatostatin receptors was recently found to be probably involved in the uptake of radiolabeled somatostatin analogs in the kidney [19]. Further studies are necessary to analyze exact mechanisms of the renal uptake and to determine the significance of the individual transport mechanisms for renal accumulation of receptor-specifi c peptides.…”
Section: Introductionmentioning
confidence: 99%